Aplikasi Kultur Campuran (Lactobacillus fabifermentans dan Aspergillus sp.) Pada Modifikasi Tepung Jagung Dengan Metode Fermentasi Terkontrol yang Dilanjutkan Dengan Pragelatinisasi - Andi Sukainah; Reski Praja Putra; Ratnawaty Fadilah; Yeni Yuliawati (Seminar Nasional LP2M UNM, 2019)
Abstract. This study aims to determine the effect of mixed culture concentrations (Lactobacillus fabifermentans and Aspergillus sp) on the physicochemical properties of cornflour. This research is a quantitative (experimental) study using the Completely Randomized Design (CRD) method. The concentration of mixed cultures (L. fabifermentans and Aspergillus sp) became the treatment variables in this study. The treatments consisted of four concentrations of mixed cultures (L. fabifermentans: Aspergillus sp) namely (1: 0), (1: 1), (1: 2) and (1: 3) by fermentation for 24 hours. After going through the fermentation process, the pragelatinization process is carried out on corn flour, 500 g of corn flour is added with 30% distilled water (150 ml) and steamed for 15 minutes in a steaming pot at 80˚C. The parameters observed were the pH value in the fermented liquid, while the cornflour was analyzed for water content, amylose content, starch content, viscosity, and rheology. Data analysis technique used was analysis of variance which was further processed using SPSS version 22. The results showed that the best treatment resulted from the treatment with the addition of mixed culture concentrations of L. fabifermentans: Aspergillus sp (1: 3) with a liquid pH value of 3.60, water content 2.12%, amylose content 17.42%, starch content 65.31%, viscosity 1825 cps with rheological properties included in the non-Newtonian category (pseudoplastic flow) Keywords: Cornflour, Lactobacillus fabifermentans, Aspergillus sp, fermentation, pragelatinization